ANALISIS ISI KUANTITATIF KEKERASAN DALAM FILM THE DOLL 3 - Fadia (2023)
The phenomenon of violence that occurs in the media, especially in films, is increasing. This study discusses violence in a film. Mass media, such as film, are growing with a fast and wide spread, so that everyone can enjoy it anywhere, and of course, can have a negative impact on showing violent films. Aggressive behavior as a result of watching violent films is often found in reality. Shows on the Netflix video web are also many films containing violent content such as the one in the horror film entitled "The Doll 3". This study aims to determine the frequency and tendency of violence in the film The Doll 3. This type of research is descriptive quantitative and content analysis research methods using cultivation theory. The categorization of nonverbal and verbal violence is used as Eriyanto's content analysis theory and as an object of his research, namely the film "The Doll 3 2022" which uses the main role of the doll. The results of this study are the overall frequency of nonverbal violence categories, namely hitting 15 scenes, injuring 28 scenes, killing 23 scenes, and using sharp weapons 25 scenes. The frequency results for the category of verbal violence as a whole were Rude 12 places, Swearing 3 places, Threatening 14 places and 10 places being closed.